2015
DOI: 10.4314/ijbcs.v8i5.18
|View full text |Cite
|
Sign up to set email alerts
|

Sedative properties of <i>Mitracarpus villosus</i> leaves in mice

Abstract: The leaves of Mitracarpus villosus (Sw.) DC. (Rubiaceae) have several therapeutic applications in the West African folk medicine for the management of a plethora of stress-related diseases including headaches. This study was designed to evaluate the sedative properties of the ethylacetate extract of Mitracarpus villosus on open field (OFT), diazepam-induced sleep, staircase climbing, head-dips in the hole-board test and rota rod test in mice. Graded doses (100 -400 mg/kg) of the extract significantly and dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For instance, studies have shown that the leaf extract of M. vilosus using different solvent fractions like methanol, acetone ethanol, n-hexane, and ethyl acetate yielded secondary metabolites like terpenoids, phenols, tannins, cardiac glycosides, and carbohydrates (23,24). John-Africa and colleagues investigated the effect of the sedative properties of M.villosis leaves in mice, and observed the presence of psychoactive substances that are sedative in nature, then concluded that M.villosus leaf can be used as a therapeutic agent in the management of stress-related diseases (25). The crushed leaves of M. villosus have also been shown to be beneficial in the treatment of ulcers, ringworms, eczema, and fresh wounds which could be due to its antibacterial and anti-ulcerative properties (24).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies have shown that the leaf extract of M. vilosus using different solvent fractions like methanol, acetone ethanol, n-hexane, and ethyl acetate yielded secondary metabolites like terpenoids, phenols, tannins, cardiac glycosides, and carbohydrates (23,24). John-Africa and colleagues investigated the effect of the sedative properties of M.villosis leaves in mice, and observed the presence of psychoactive substances that are sedative in nature, then concluded that M.villosus leaf can be used as a therapeutic agent in the management of stress-related diseases (25). The crushed leaves of M. villosus have also been shown to be beneficial in the treatment of ulcers, ringworms, eczema, and fresh wounds which could be due to its antibacterial and anti-ulcerative properties (24).…”
Section: Discussionmentioning
confidence: 99%
“…That is when mice were rolled sideways and could not stand upright using all four limbs (Miya et al, 1973). The first parameter was decrease in latency of sleep as shown by Crinum zeylanicum (Tijani et al, 2012a) and Gymnema sylvestre (James et al, 2014). The second parameter assessed was increase in the duration of sleep as seen in Hippocratea Africana (Okokon et al, 2014) and Homalium letestui (Okokon and Davies, 2014) all indicating sedative activity.…”
Section: (Iv) Phenobarbitone Induced Sleeping Time (Pist)mentioning
confidence: 99%
“…Secondary metabolites : Various studies have identified the presence of important classes of secondary metabolites in the plant. Flavonoids, tannins, terpenoids, phenols, resins and carbohydrates were detected in M. Villosus according to [25]. Furthermore, Saponin and alkaloid are present in the crude extract of M. villosus according to [26].…”
Section: Phytochemistrymentioning
confidence: 99%